WANITA KARIR DALAM PERSPEKTIF HUKUM ISLAM - Fajarwati Fajarwati (Sekolah Tinggi Ilmu Syariah Al-Hilal Sigli Aceh- Indonesia, 2019)
Today the need for life and the trend of life inevitably must be followedeven become an obligation for women to help with family life. In work mattersthere are sometimes no separations between men and women. At present, manyurgent positions are filled by women such as strategic positions, this is due to lackof honesty from men and often misused positions in work. Women are morehonest in working, disciplined, fast and right in taking policies. Today manyadvanced companies are led by career women. The career woman referred to hereis a woman who has a family and is more focused on her profession than a family.Where these women have two major responsibilities, namely family (home,husband and child) and office. By carrying out these two responsibilities at onetime, it requires energy and thought and strategy in doing so. Career women canlive outside due to technological assistance. Women are known for three things,wells, kitchens and mattresses. Now these three things can be run well thanks tothe technology without the need for a lot of time. However, children's problemscannot be controlled by technology. The right choice to control children is toprovide children's education in advanced schools that have been provided by thestate and the private sector. In addition, career women must use the pattern ofeducating people first, namely providing special time to teach and educatechildren at night and instill religious knowledge. strong in children. In Islamiclaw, women are allowed to have a career provided that they have permission fromtheir husbands and do not neglect their responsibilities as mothers.